2002
DOI: 10.1037/0033-295x.109.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Genes, interactions, and the development of behavior.

Abstract: Explaining how genes influence behavior is important to many branches of psychology, including development, behavior genetics, and evolutionary psychology. Presented here is a developmental model linking the immediate consequence of gene activity (transcription of messenger RNA molecules from DNA sequences) to behavior through multiple molecular, cellular, and physiological levels. The model provides a level of detail appropriate to theories of behavioral development that recognizes the molecular level of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(102 citation statements)
references
References 70 publications
0
96
0
6
Order By: Relevance
“…Gene-environment interactions have inspired much recent enthusiasm among social scientists (F. Collins 2004;Johnston and Edwards 2002). Gene-environment interactions imply that the same environmental cause has different effects for individuals who differ in key elements of G. As just discussed, the possible pervasiveness of gene-environment interactions suggests that genetic differences may commonly intrude into explanations specifically in trying to understand why some individuals seem to be more influenced by particular environmental causes than others.…”
Section: Social Causes Of Genomic Causesmentioning
confidence: 99%
“…Gene-environment interactions have inspired much recent enthusiasm among social scientists (F. Collins 2004;Johnston and Edwards 2002). Gene-environment interactions imply that the same environmental cause has different effects for individuals who differ in key elements of G. As just discussed, the possible pervasiveness of gene-environment interactions suggests that genetic differences may commonly intrude into explanations specifically in trying to understand why some individuals seem to be more influenced by particular environmental causes than others.…”
Section: Social Causes Of Genomic Causesmentioning
confidence: 99%
“…Perrin and Lee (2007) argue that gene-environment interaction studies need to understand that "interconnections between individuals and social structures can predict important variations in individual behavior without recourse to individual traits" and thus "environments and genetic potentials must be understood as nested and cross-cutting in potentially complex ways" (311). Nevertheless, the bulk of gene-environment studies continue to focus on the social and demographic characteristics of individuals or families rather than on the composition of larger social contexts such as neighborhoods or schools ) and yet studies at this higher level of aggregation speak more directly to theories of geneenvironment interactions (Johnston and Edwards 2002;Shanahan and Hofer 2005;Perrin and Lee 2007). This perspective is particularly relevant when one considers the social pressures responsible for school and neighborhood segregation by race (Massey and Denton 1993).…”
Section: In the Introduction To Behavior Genetic Approaches In Behavimentioning
confidence: 99%
“…In addition to the numerous studies that have employed experimenter-delivered reinforcement, research has also demonstrated that automatic reinforcement (Vaughan & Michael, 1982) can strengthen vocal behavior in children (e.g., Carroll & Klatt, 2008;Miguel, Carr, & Michael, 2001/2002Smith, Michael, & Sundberg, 1996;Sundberg, Michael, Partington, & Sundberg, 1996;Yoon, 1998;Yoon & Bennett, 2000). Unlike direct reinforcement, which requires the deliberate delivery of reinforcement by another person, automatic reinforcement occurs without the direct mediation of another (Vaughan & Michael).…”
Section: Mythmentioning
confidence: 99%
“…More recently, the partitioning of nature and nurture has been eschewed and, in its place, interactionism has become the doctrine professed by many developmentalists (e.g., Anastasi, 1958;Johnston, 1987Johnston, , 1988Johnston, , 2002Moore, 2001) within the life sciences. According to Anastasi, efforts to determine the relative contributions of nature and nurture have not been successful.…”
mentioning
confidence: 99%